Desarrollo de aplicación Web para el seguimiento de proyectos de grado de Tecnología en Desarrollo de Software en UNIMINUTO Vicerrectoría Regional Orinoquía - Quevedo García, Bryam Alí; Moreno Murillo, Jhon Stewar; Parra Joven, Andrés Eduardo (Corporación Universitaria Minuto de Dios, 2021)
Este proyecto consistió en el desarrollo de una aplicación web que contiene un repositorio de ideas de proyectos de grado y una serie de módulos para llevar el control de los proyectos y anteproyectos de grado de los estudiantes del programa de Tecnología en Desarrollo de Software de la Corporación Universitaria Minuto de Dios, Vicerrectoría Regional Orinoquia. De este modo, con el proyecto se busca optimizar los procesos realizados por el líder de investigación del Tecnología en Desarrollo de Software, a la hora de registrar ideas de anteproyectos de grado, asignar asesores, asignar jurados, generar reportes y consultar el estado de los proyectos, creando una trazabilidad en los diferentes procesos de proyectos de grado permitiéndole a los asesores y estudiantes la retroalimentación mutua.

This project consisted of the development of a web application that contains a repository of ideas for degree projects, and it also has a series of modules to keep track of the projects and preliminary degree projects of the students of the Software Development Technology program of the Corporación Universitaria Minuto de Dios, Vicerrectoría Regional Orinoquia. In this way, the project seeks to optimize the processes carried out by the research leader of the Software Development Technology program, when registering ideas for preliminary degree projects, assigning advisers, assigning juries, generating reports and consulting the status of the projects; thus improving traceability in the different processes of degree projects and allowing advisors and students to record the mutual feedback that is carried out in each review of the preliminary project or the final report. On the other hand, the development of the web application was carried out using technologies such as PHP, JavaScript, CSS, HTML. Then, during the planning process, the functional and non-functional requirements were raised, in the design stage the mockups and the entity-relationship diagram of the database were designed, in the coding stage the database was made in MySQL, and as Integrated Development Environments MySQL Workbench and Visual Studio Code were used. Regarding the development stage, it can be indicated that the agile development methodology known as Extreme Programming (XP) was used, with which the application was developed in approximately 12 weeks through four phases: planning, design, coding and testing. Hence, the implementation of the application allows to provide agility and security in each project development process, since it serves to store ideas of preliminary projects that were previously discarded, so that students from other semesters can retake them, thus eliminating many of the difficulties such as difficulty when they are finding a project idea or the inability to quickly know if the idea has already been developed previously by other students.
Desarrollar una aplicación web para el seguimiento de anteproyectos y proyectos de grado del Programa de Tecnología en Desarrollo de Software en la Corporación Universitaria Minuto de Dios, Vicerrectoría Regional Orinoquía.
Keywords: Anteproyecto de grado; Proyecto de grado; Aplicación web; Base de datos; Preliminary project; degree project; technology; degree work; web application; database